2016
DOI: 10.1093/jee/tow208
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating High Release Rate MCH (3-Methylcyclohex-2-en-1-one) Treatments for ReducingDendroctonus pseudotsugae(Coleoptera: Curculionidae) Infestations

Abstract: Current recommendations for applying the antiaggregation pheromone 3-methylcyclohex-2-en-1-one (MCH) to protect live trees from Douglas-fir beetle, Dendroctonus pseudotsugae Hopkins, infestation are to space individual passive releasers (MCH bubble capsules) on a 12- by 12-m grid throughout areas to be protected. Previous field studies and a theoretical study using a puff dispersion model to predict pheromone concentrations have shown that releasers emitting higher rates of MCH spaced farther apart may be as e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Although the model used predicts significant behavioural response beyond 12 m from a releaser, the effect is apparently not strong nor consistent enough to totally prevent dispersing adults from initiating colonisation of suitable host trees. The data reported here may help researchers to understand more precisely the relationships between effective spatial arrangements of release devices (Ross et al 2002;Ross and Wallin 2008;Brookes et al 2016) and Douglas-fir beetle behaviour.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Although the model used predicts significant behavioural response beyond 12 m from a releaser, the effect is apparently not strong nor consistent enough to totally prevent dispersing adults from initiating colonisation of suitable host trees. The data reported here may help researchers to understand more precisely the relationships between effective spatial arrangements of release devices (Ross et al 2002;Ross and Wallin 2008;Brookes et al 2016) and Douglas-fir beetle behaviour.…”
Section: Discussionmentioning
confidence: 88%
“…Current recommendations are to place individual releasers on a 12 m × 12 m grid throughout the area to be protected. Despite the many publications demonstrating the efficacy of MCH for protecting trees Daterman 1994, 1995a;Ross et al 1996Ross et al , 2002Ross and Wallin 2008;Brookes et al 2016) and a large number of successful operational treatments over the past 20 years, the specific mechanism of action on bark beetle behaviour or the dispersal characteristics of MCH in forested environments are not fully understood. The objective of the present study was to evaluate Douglas-fir beetle response to individual MCH releasers at varying distances from the source to gain further insight into the spatial dynamics of MCH effects on Douglas-fir beetle behaviour in light of existing recommendations for operational MCH treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Ross et al (1996) found that application rates of 20 and 40 g AI/ha reduced attack to one fifth the level in untreated stands, and Ross and Wallin (2008) reported that applications of 30 g AI/ha, at two different spatial arrangements, also reduced attack rates to zero. Other more recent research also indicates that application using bubble caps can be equally effective using fewer bubble caps/ha while maintaining the weight of AI/ha constant (Brookes et al, 2016;Strand et al, 2012). Such an approach would greatly reduce the cost of application, because labour is a large part of the cost of treatments.…”
Section: Discussionmentioning
confidence: 99%
“…A modelling exercise using a plume dispersion model and results of previous field studies suggested that MCH release rates up to six times the standard rate at correspondingly wider spacing would be effective for preventing Douglas-fir beetle infestation (Strand et al 2012). A subsequent field study found that MCH release rates up to seven times the standard at wider spacings were as effective as deploying individual bubble capsules on a 12 m × 12 m grid (Brookes et al 2016). However, because the field studies demonstrate collectively that the threshold of effectiveness is somewhere between seven and nine times the release rate of individual bubble capsules, current recommendations are to not go beyond about four to five times the standard release rate in operational applications to provide a margin of error (Ross et al 2015).…”
Section: Early Research On Bark-pheromone Identificationmentioning
confidence: 98%